2021
DOI: 10.1108/jfra-06-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting disclosure in Malaysia: regulations and practice

Abstract: Purpose Integrated reporting (IR) is a new trend in corporate reporting that has spread rapidly in recent years for disclosing financial and non-financial information. This study aims to assess the status of the current regulations and the trends in IR disclosure practice in an emerging market, Malaysia, by providing a comparative analysis of the IR disclosure level (IRDL) and IR disclosure quality (IRDQ). Design/methodology/approach The current study has developed a comprehensive IR disclosure index based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Wahl et al (2020) also found IR disclosure has an insignificant association with firm value and earnings forecast accuracy. Qaderi et al (2023) analysed Malaysian listed firms and found IR disclosure levels and quality were significantly improved. Soriya and Rastogi (2023) examined 93 annual reports of Indian companies and found IR quality disclosure is considerably related to firms’ profitability while having an insignificant relationship with firms’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wahl et al (2020) also found IR disclosure has an insignificant association with firm value and earnings forecast accuracy. Qaderi et al (2023) analysed Malaysian listed firms and found IR disclosure levels and quality were significantly improved. Soriya and Rastogi (2023) examined 93 annual reports of Indian companies and found IR quality disclosure is considerably related to firms’ profitability while having an insignificant relationship with firms’ performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Further, it is argued as in the Malaysian market, IR adoption is still voluntary, and only a handful of companies have adopted IR techniques. Qaderi et al (2021) analyse data from 267 company-year observations between 2017 and 2019 found that the number of Malaysian companies preparing IR in accordance with the IIRF is on the rise with significant differences between large and minor companies' IR practises. Qaderi et al (2021) also argue that the recommendation of the Malaysian code of corporate governance in 2017 has affected the implementation of IR.…”
Section: Literature Review the Existing Level Of Ir Adoptionmentioning
confidence: 99%
“…Content analysis was used to measure IR disclosure. This technique has been widely used in IR disclosure research, e.g., [4,17,[99][100][101]. A checklist containing 100 items was constructed based on the IIRF, and divided into four sub-categories: background, form, content, and assurance and reliability.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The quantity of IR information refers to the extent to which the information disclosed matches the IR disclosure index [107]. IRD_Quan was measured on a binary scale (an unweighted scoring method) that assumed a value of "1" if the company disclosed the IR item in its annual report and "0" otherwise [17,99,107]. The scores were then aggregated to obtain the total score of each category of IR.…”
Section: Dependent Variablesmentioning
confidence: 99%